Kewenangan Majelis Kehormatan Mahkamah Konstitusi Mengadili Hakim Mahkamah Konstitusi (Dalam Pelanggaran Kode Etik Hakim Mahkamah Konstitusi) - Melkianus Umbu Deta; I Nyoman Suandika; Ida Bagus Anggapurana Pidada (Student Research Journal, 2024)
The purpose of this study is to find out and analyze the authority of the Honorary Assembly of the Constitutional Court to prosecute constitutional court judges in violation of the code of ethics of constitutional court judges. and knowing the inhibiting factors in the Honorary Assembly of the Constitutional Court adjudicating the judges of the Constitutional Court in violation of the code of ethics of the judges of the Constitutional Court.The method used in the preparation of this study is a juridical-normative approach. The juridical-normative approach is a research that focuses or examines the application of legal norms or rules in positive law. In addition, we need to know, juridical-normative research focuses on literature materials and regulations that are used as the basis for preparation.The result of this study is that the Honorary Assembly of the Constitutional Court (MKMK) is a device formed by the Constitutional Court to monitor, examine, and recommend actions against Constitutional Judges who are suspected of violating the code of ethics and code of conduct of constitutional judges. The types of violations examined, including committing reprehensible acts, not attending the trial which is his duty and obligation for 5 times in a row, Violating the oath or promise of office, Deliberately obstructing the Constitutional Court to give a decision within the time as referred to in Article 7B paragraph (4) of the 1945 Constitution, Violating the Code of Ethics and Conduct of Constitutional Judges, Violating the prohibition as a Constitutional Judge, Not carrying out his obligations as a Constitutional Judge